Muscular power, neuromuscular activation, and performance in shot put athletes at preseason and at competition period - Kyriazis, T. A.; Terzis, G.; Boudolos, K.; Georgiadis, G. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to investigate changes in shot put performance, muscular power, and neuromuscular activation of the lower extremities, between the preseason and the competition period, in skilled shot put athletes using the rotational technique. Shot put performance was assessed at the start of the pre-season period as well as after 12 weeks, at the competition period, in nine shot putters. Electromyographic (EMG) activity of the right vastus lateralis muscle was recorded during all shot put trials. Maximum squat strength (1RM) and mechanical parameters during the countermovement jump (CMJ) on a force platform were also determined at pre-season and at competition period. Shot put performance increased 4.7% (p < 0.05), while 1RM squat increased 6.5% (p < 0.025). EMG activity during the delivery phase was increased significantly (p < 0.025) after the training period. Shot put performance was significantly related with muscular power and takeoff velocity during the CMJ, at competition period (r = 0.66, p < 0.05 and 0.70, p < 0.05), but not with maximum vertical force. One RM squat was not related significantly with shot put performance. These results suggest that muscular power of the lower extremities is a better predictor of rotational shot put performance than absolute muscular strength in skilled athletes, at least during the competition period.